Cryo-electron microscopy of the chromatin fiber. (October 2020) - Boopathi, Ramachandran; Dimitrov, Stefan; Hamiche, Ali; Petosa, Carlo; Bednar, Jan
Highlights: Cryo- electro microscopy reveals the native conformation of chromatin fiber both in vitro and in situ. Presence of linker histone and ionic conditions determines the level of fiber compaction and organization. Variability of native chromatin hampers the determination of its high resolution 3D structure. Highly diverse conformations observed for chromatin fibers underscore the great structural plasticity of chromatin. Abstract : The three-dimensional (3D) organization of chromatin plays a crucial role in the regulation of gene expression. Chromatin conformation is strongly affected by the composition, structural features and dynamic properties of the nucleosome, which in turn determine the nature and geometry of interactions that can occur between neighboring nucleosomes. Understanding how chromatin is spatially organized above the nucleosome level is thus essential for understanding how gene regulation is achieved. Towards this end, great effort has been made to understand how an array of nucleosomes folds into a regular chromatin fiber. This review summarizes new insights into the 3D structure of the chromatin fiber that were made possible by recent advances in cryo-electron microscopy.